EVALUATION OF OPEN HIGHER EDUCATION PROGRAMS IN TURKEY - Sen, Engin Tamer; Cekerol, Kamil (PEOPLE: International Journal of Social Sciences, 2018)
In the development of open and distance education, the formation of open universities constitutes an important milestone. What is expected from those institutions called “mega universities”, with their large scale economies as a result of their high number of students, is that they provide this large mass of students with low-cost and high-quality higher education. This role can be undertaken by an open university in every country. However, besides Anadolu University, which used to be the only institution in Turkey in this field for many years, Istanbul University and Atatürk University also have been active in open education since 2011. The motivation of this study is to evaluate the development processes of these universities that have more than one hundred thousand students. For this purpose, the following are evaluated and interpreted: The place of undergraduate and graduate programs offered in these three universities in all university programs; their different practices in associate degree and undergraduate programs; quota restrictions and enrollment numbers in programs; and program diversities. In the scope of this study, relevant data from the last ten years of higher education manuals were collected, and the university web pages were examined. Findings in the study show that sufficient program diversity has not been achieved, and high quota restrictions decreased the student numbers of these universities. The ways of achieving program diversity and overcoming quota constraints by considering "quality" and "requirements" are the subjects of more detailed further researches.